2013
DOI: 10.1080/10410236.2013.794412
|View full text |Cite
|
Sign up to set email alerts
|

Framing Medical Tourism: An Analysis of Persuasive Appeals, Risks and Benefits, and New Media Features of Medical Tourism Broker Websites

Abstract: This study explores the benefits and risks featured in medical tourism broker websites, as well as the types of persuasive appeals that these websites use to attract potential customers, from a framing theory perspective. In addition, it examines relationships among types of appeals and specific types of health-related services offered by medical facilities abroad and the role of new media modalities within medical tourism broker sites. A content analysis of 91 medical tourism broker websites was conducted. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Although frequently promoted on health travel websites [28], as the number of accredited organizations focused on health travel increase, international accreditation may not be a long-term source of competitive advantage for providers seeking to care for health travelers. As accreditation becomes an expectation, creation of high levels of brand trust via marketing and loyalty through positive word-of-mouth are likely to become the key drivers of a health travel provider’s success [60,61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although frequently promoted on health travel websites [28], as the number of accredited organizations focused on health travel increase, international accreditation may not be a long-term source of competitive advantage for providers seeking to care for health travelers. As accreditation becomes an expectation, creation of high levels of brand trust via marketing and loyalty through positive word-of-mouth are likely to become the key drivers of a health travel provider’s success [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Each result from the first 10 pages of these searches was reviewed to meet the criteria of: (1) a narrative written in English because all researchers were fluent in this language, (2) a first-person narrative written by an individual who underwent treatment and/or their significant other/partner on the trip, (3) included a description of the type of procedure, (4) a narrative that included a personal actual experience of health travel to Turkey, and (5) a narrative that was publicly available and did not require a password or discussion board membership to read. The authors reviewed all narratives to ensure promotional narratives found on health travel facilitator, promoter, or health care provider sites were excluded to avoid potential bias [28]. All narratives selected noted the name of the procedure performed and mentioned that this procedure was performed in Turkey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Some of the main reasons for medical tourists going overseas to receive medical treatments are: immediate and high quality medical services, opportunity to travel to other countries or exotic destinations, flexibility in arranging medical services overseas, and high health insurance premiums in their home countries. 7,8 In addition, overseas healthcare providers are often more willing to provide medical tourists with an upfront estimate of the medical treatment. Hence, for medical tourists, medical tourism offers an inexpensive alternative for receiving medical treatment overseas without compromising on quality.…”
Section: Medical Tourismmentioning
confidence: 99%
“…It is estimated that 3-4% of the world population already travels abroad for medical treatment (ITB Berlin, 2012). With this trend, research on medical tourism has increased significantly in recent years Lee et al, 2014). However, the research has focused more attention on the growing supply side of the industry than the demand side (Gan and Frederick, 2013).…”
Section: Introductionmentioning
confidence: 99%